INFLUENCE OF COUNSELING ABOUT COLOSTRUM ON THE KNOWLEDGE OF PREGNANT WOMEN IN PMB MOJOROTO DISTRICT KEDIRI CITY - Uskenat, Kristavera (Universitas Kadiri, 2021)
One of the causes of high infant mortality is malnutrition, which can be avoided by breastfeeding, starting with colostrum. Colostrum is the first breast milk to supply various immune and growth factors to ensure the survival and health of the newborn. The research objective was to determine the effect of counseling on colostrum on the knowledge of pregnant women at PMB Ny.